2010
DOI: 10.2478/v10007-010-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Box-Behnken experimental design in the development of pectin-compritol ATO 888 compression coated colon targeted drug delivery of mesalamine

Abstract: A novel oral colon-specific drug delivery system (CDDS) has been developed as one of the site-specific drug delivery systems. This delivery system, by means of combining one or more controlled release mechanisms, hardly releases the drug in the upper part of the gastrointestinal (GI) tract, but rapidly releases drug in the colon following oral administration. The necessity and advantage of CDDS have been recognized and reviewed recently (1-3). Owing to CDDS specifically delivering the drug to the colon, many b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After the 10 th days postoperation, there was complete healing occurred in the A. vera based SSD cubogel with the formation of natural skin, while 70-80% healing occurred in cubogel with SSD and both has faster healing as compared to marketed preparation. [ 42 46 47 48 49 ] In vivo wound, healing study revealed that the cubogel with drug and A. vera shows no scar formation after healing because of antiscaring effect of A. vera and generate normal skin without scaring. [ 50 ] In marketed formulation, the pseudoeschar formed during the healing which hindered the permeation of drug so delay in healing and sometimes leading to infection in the wound.…”
Section: Resultsmentioning
confidence: 99%
“…After the 10 th days postoperation, there was complete healing occurred in the A. vera based SSD cubogel with the formation of natural skin, while 70-80% healing occurred in cubogel with SSD and both has faster healing as compared to marketed preparation. [ 42 46 47 48 49 ] In vivo wound, healing study revealed that the cubogel with drug and A. vera shows no scar formation after healing because of antiscaring effect of A. vera and generate normal skin without scaring. [ 50 ] In marketed formulation, the pseudoeschar formed during the healing which hindered the permeation of drug so delay in healing and sometimes leading to infection in the wound.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid matrix tablets [8] containing lipid excipients having a melting point higher than 40° and a low polarity are used to sustain drug release [9] . Among such lipids, glyceryl dibehenate (Compritol ® 888 ATO, melting point ranging from 69° to 74° and hydrophilic-lipophilic value of 1) was originally introduced as a lubricant [10] but is now widely used by various techniques to obtain sustained-release tablets: direct compression [11][12][13][14][15][16][17] , wet granulation [18,19] , melt granulation [12][13][14]16,[20][21][22][23] , hot-melt coating [24] , and hot-melt extrusion [25,26] .…”
Section: Research Papermentioning
confidence: 99%
“…Chemically, it is 2-[(2-amino-6-oxo-1,6-dihydro-9 H -purin-9-yl)methoxy]ethyl L-valinate ( Figure 1A ), used for the treatment of herpes simplex and herpes zoster. It is phosphorylated by viral thymidine kinase to acyclovir triphosphate (the active metabolite) which then inhibits herpes viral DNA replication by competitive inhibition of viral DNA polymerase, and by incorporation into and termination of the growing viral DNA chain [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factorial experiments find extensive applications in all research fields which allow the investigation of multiple factors simultaneously and also the examination of one factor at different levels of the other factor or factors. The Box-Behnken experimental design (BBD), developed by Box and Behnken in 1980 is a useful response surface methodology, where the level of one of the factors is fixed at the centre level while combinations of all the levels of the other factors are applied [ 8 10 ]. Extensive literature surveys have reported several analytical techniques for the estimation of VCR in both bulk and dosage forms [ 11 23 ].…”
Section: Introductionmentioning
confidence: 99%